KEBANGKITAN HADIS DI INDIA: STUDI HISTORIOGRAFI HADIS ABAD 12-14 HIJRIAH - Hafidhuddin Hafidhuddin (Jurnal Studi Hadis Nusantara, 2022)
This research focuses on the development of hadith studies in the Indian Subcontinent in the 12th-14th. India and its scholars have played a role and contribution to Islamic civilization. From that, there are two problems that are then raised. First, what is the role of Indian scholars in the process of developing hadith and its distribution? Second, what is the method of Indian scholars in compiling a number of works in the field of hadith? Thus the purpose of this study outlines the development of Islam in India and the contribution of Indian scholars in the study of hadith. In addition, explain what methods indian scholars use in exploring the hadiths of the Prophet SAW. Based on that, the approach of history as a research method. As a result, for Indian scholars the process of spreading the hadith of the Prophet SAW along with developing the teachings of Islam, considering the hadith of the second most important source after the Qur'an. Departing from that also the tendency to do sharah and hasyiah for the poles of al-sittah is encouraged, not limited to writing works, publishing, and publishing. However, various studies continue to be encouraged so that students, and the public can participate in understanding the teachings of Islam until the 12th-14th, even today India is still a center of hadith studies in the Islamic world.